Evaluation of treatment costs for direct versus stepwise admission to home treatment - Kaehlitz, Antonia; Dang, Michel Ngoc-Minh; Kronschnabel, Jens; Pichler, Eva-Maria; Hepp, Urs; Walter, Marc; Zavorotnyy, Maxim (Frontiers in Psychiatry, 2025)
BackgroundMental health care’s rising socio-economic relevance has led to a need for cost-effective treatment alternatives. Home Treatment (HT) has emerged as a viable substitute for inpatient psychiatric care, introduced by the Psychiatric Services Aarau AG (PDAG) in 2015. Subsequent studies have evaluated its impact on hospital bed usage and treatment costs. This study aimed to assess the long-term effects of HT after its full integration into routine psychiatric care.MethodsAn observational study included patients who received HT between 2019 and 2020. They were followed for two years, comparing cumulative costs, treatment duration, and readmission rates with a matched inpatient control group. Subgroup analyses distinguished between patients directly admitted to HT and those transitioning from inpatient care. Statistical analyses included Wilcoxon signed-rank tests and Fisher’s exact tests.ResultsHT patients had fewer inpatient days but longer total treatment durations; costs did not differ significantly. However, analyses revealed that direct admission to HT was linked to a 24% cost reduction and a lower readmission rate compared to inpatient care. In contrast, combining inpatient care with HT led to increased treatment durations and costs.ConclusionHT as a standalone treatment showed cost efficiency and reduced readmission rates, positioning it as a promising alternative to inpatient care. However, combining HT with inpatient treatment increased duration and costs, undermining the financial benefits. Future research should identify patient groups that benefit most from direct HT admission and explore hybrid models integrating short-term inpatient interventions followed by HT to enhance cost-effectiveness and clinical outcomes.